(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This research seeks to test "the effect of entrepreneurship as an independent variable and its components (creativity, adventure, and strategic innovation) and sustainable competitive performance as a dependent variable and its components (reducing delivery cycle time, rapid response to market demand, increasing customer satisfaction, providing the best quality, increasing market share)" through A field study, and here the research problem was diagnosed in an attempt to answer the following question: Is there awareness among senior management within the private colleges (researched) of the importance of employing entrepreneurship in sustainable competitive performance? “Because of the importance of the private education sector, and from this field, the researcher chose private colleges as a research community, which are numbered according to statistics recognized by the Ministry of Higher Education and Scientific Research for the academic year (2022-2023), as the number of private universities and colleges reached (72) universities and private colleges. As for the number The universities and private colleges located in the city of Baghdad reached (33) universities and private colleges, and the research community chose the research community that was established more than 20 years ago to obtain sustainable competitive performance in it, and it was conducted in six private colleges located in Baghdad, which are (University Heritage College, University College Al-Mansour University, Al-Rafidain University College, Al-Mamoun University College, Baghdad University College of Economic Sciences, Baghdad College of Medical Sciences (formerly Baghdad Pharmacy). The research sample consists of (87) individuals from the deans of the colleges and their assistants, as well as the heads of scientific and administrative departments. The researcher has adopted the method Descriptive and analytical, as the questionnaire was used as the main tool for collecting data related to the applied aspect, and the data was analyzed and hypotheses were tested using appropriate statistical tools, and then the data obtained was processed with a number of statistical tools and methods, which were divided into the following totals: (arithmetic mean, standard deviation, coefficient Difference, simple linear regression, multiple regression) and the ready-made software package (SPSS and AMOS) was used. The results showed that there is an effect between entrepreneurship and its dimensions and competitive performance and its dimensions.